Premier engineering college : the MBA conundrum - Sharma, Vinod, 1978-; Kapse, Manohar; Sanjeev, MA; Poulose, Jeanne; Mahajan, Yogesh (London : SAGE Publications: SAGE Business Cases Originals, 2024)
Managerial skills are highly valued in India, leading to a significant demand for management education. Premier Engineering College (PEC), known for its engineering program, introduced the Post-Graduate Diploma in Management (PGDM) in 2000. While initially successful, the MBA program's performance has been declining, with below-average growth in placement packages (PEC's compounded annual growth rate is 8%, compared to 11% for MBA programs as a whole in India) and reduced demand for the courses. The college's admissions team faced challenges in recruiting high-quality students, resulting in less desirable placements. Unlike the engineering program, MBA admissions allowed the college to design its own selection process and criteria based on recruiter feedback. The newly appointed PEC director, Professor (Dr) B. K. Verma, is anxious about the downward trend. Therefore, to attempt to reverse the poor trend and uphold PEC's reputation, he has formed a committee to gather and analyze information, and to come up with a plan to boost placements and admissions.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Marketing research -- India -- Case studies; Management science -- India -- Case studies; Business schools -- India -- Case studies -- Case studies